2009
DOI: 10.1186/1471-2407-9-432
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HIF-1alpha and VEGF in colorectal cancer: association with clinical outcomes and prognostic implications

Abstract: BackgroundHypoxia-inducible factor 1 alpha (HIF-1α) and vascular endothelial growth factor (VEGF) are frequently overexpressed in numerous types of cancers and are known to be important regulators of angiogenesis. Until now, few studies have been carried out to investigate the prognostic role of these factors in solid tumors, especially in colorectal cancer (CRC). The purpose of this study was to evaluate the expression of HIF-1α and VEGF in CRC tissues, and to analyze the association of these two factors with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
142
2
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(164 citation statements)
references
References 28 publications
13
142
2
7
Order By: Relevance
“…Vascular endothelial growth factor (VEGF) is a key regulator of angiogenesis and it has been extensively studied for its role in the invasion and metastasis of cancer cells (Wang et al, 2008). Previous research suggested expression of VEGF was positively observed in the CRC patients, and VEGF status was significantly associated with tumor stage, lymph nodes and liver metastases (Zafirellis et al, 2008;Cao et al, 2009). Identically, our results demonstrated VEGF was significantly higher expressed in liver metastasis than that in non metastasis colorectal cancer, with 94.1% positive in liver metastasis group and 65.2% positive in non metastasis group.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is a key regulator of angiogenesis and it has been extensively studied for its role in the invasion and metastasis of cancer cells (Wang et al, 2008). Previous research suggested expression of VEGF was positively observed in the CRC patients, and VEGF status was significantly associated with tumor stage, lymph nodes and liver metastases (Zafirellis et al, 2008;Cao et al, 2009). Identically, our results demonstrated VEGF was significantly higher expressed in liver metastasis than that in non metastasis colorectal cancer, with 94.1% positive in liver metastasis group and 65.2% positive in non metastasis group.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Cao D et al (Cao D et al, 2009). the VEGF and HIF-1α expressions of patients with operated colorectal cancer were studied regarding survival according to intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Wide variation of as low as 2.8% to 9.9% for protein concentration in milled rice germplasm lines of Chhattisgarh have been reported by Chandel et al, (2005). Cao et al, (2009) found a wide variation in the levels of storage protein content (7.38-15.41%) in Chinese varieties of O. sativa rice.…”
Section: Total Protein Contentmentioning
confidence: 93%
“…The earlier workers Kennedy and Burlingame (2003), Cao et al, (2009), Silveira et al, (2010 proposed a classification for the protein contents as high (≥12%), medium (11.9-9%), and low (≤8.9%). Based on the range of protein content present in our association mapping panel, classification of high (>10.5g/100g), moderate (9.01-10.5g/100g) and low levels of proteins (<9.0g/100g) is followed.…”
Section: Total Protein Contentmentioning
confidence: 99%